Stability of positively charged nanoemulsion formulation containing steroidal drug for effective transdermal application - Da Costa, Stephanie; Basri, Mahiran; Shamsudin, Norashikin; Basri, Hamidon (Hindawi Publishing Corporation, 2014)
This paper emphasizes the formation of a positively charged nanoemulsion system for steroid drugs (hydrocortisone). It is believed that positively charged nanoemulsion provides more effective penetration of the skin. Therefore in our study we focused on the incorporation of phytosphingosine which serves as a positively charged cosurfactant in the nanoemulsion system. Negatively charged nanoemulsions were formulated mainly for comparison. Freshly prepared formulations were formed with particle size less than 300 nm and showed good stability over time. The oil-in-water nanoemulsion also showed good viscosity, conductivity, and pH values. From TEM micrograph, particle size showed consistent results with the measurement using photon correlation spectroscopy. It was concluded that both positively and negatively charged nanoemulsions showed good stability and have great potential in transdermal delivery system. Though, further investigation of the drug release and drug penetration of both positively and negatively charged nanoemulsions will be studied to further prove the efficacy of nanoemulsion with hydrocortisone as a delivery system for dermal application.